Effects of electromagnetic field frequencies on chondrocytes in 3D cell‐printed composite constructs. Issue 7 (24th March 2016) - Yi, Hee‐Gyeong; Kang, Kyung Shin; Hong, Jung Min; Jang, Jinah; Park, Moon Nyeo; Jeong, Young Hun; Cho, Dong‐Woo
Abstract: In cartilage tissue engineering, electromagnetic field (EMF) therapy has been reported to have a modest effect on promoting cartilage regeneration. However, these studies were conducted using different frequencies of EMF to stimulate chondrocytes. Thus, it is necessary to investigate the effect of EMF frequency on cartilage formation. In addition to the stimulation, a scaffold is required to satisfy the characteristics of cartilage such as its hydrated and dense extracellular matrix, and a mechanical resilience to applied loads. Therefore, we 3D‐printed a composite construct composed of a polymeric framework and a chondrocyte‐laden hydrogel. Here, we observed frequency‐dependent positive and negative effects on chondrogenesis using a 3D cell‐printed cartilage tissue. We found that a frequency of 45 Hz promoted gene expression and secretion of extracellular matrix molecules of chondrocytes. In contrast, a frequency of 7.5 Hz suppressed chondrogenic differentiation in vitro . Additionally, the EMF‐treated composite constructs prior to implantation showed consistent results with those of in vitro, suggesting that in vitro pre‐treatment with different EMF frequencies provides different capabilities for the enhancement of cartilage formation in vivo . This correlation between EMF frequency and 3D‐printed chondrocytes suggests the necessity for optimization of EMF parameters when this physical stimulus is applied to engineered cartilage. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1797–1804, 2016.